Potential of ginger endophytic actinobacteria as Aedes aegypti mosquito larvicide - Lenni Fitri; Nurjanah; Yekki Yasmin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Indonesian often use ginger (Zingiber officinale) as a spice and medicine. The plant contains potent essential oils, including Kaempferol (flavonoids), which are potent insect respiratory inhibitors. Since the direct extraction of bioactive compounds from ginger needs a significant amount of biomass or plant parts, bacteria are often utilized as a substitute to increase the efficiency of the process. Actinobacteria are a group of endophytic bacteria, which have been reported to have several benefits. Therefore, this study aimed to 1) assess the potential of ginger endophytic actinobacteria as Aedes aegypti mosquito larvicide, 2) determine the number of larvae that can change into pupa, 3) examine the morphology of mosquito larvae before and after the application of the endophytic actinobacteria. Treatments were arranged as Completely Randomized Factorial Design. The isolates used were ginger rhizome endophytic actinobacteria, namely AJ1, AJ2, AJ3, AJ4, AJ5, AJ6, and AJ7, and the inoculum volumes include 0.5 mL, 1 mL, and 1.5 mL with three recurrences each. The data obtained in this study was analyzed using the Analysis of Variance (ANOVA). The results showed that AJ7 had the highest ability in causing larvae death with an average of 27.11 individuals (90.37%). The highest number of larvae becoming pupae was found in AJ3 actinobacterial isolate. Furthermore, the larvae morphology after the treatment showed transparent white body and head, a disjointed digestive tract, and a transparent siphon. Based on these results, the isolate AJ7 has the potential to be used as a biopesticide or larvicide to reduce Aedes aegypti larvae. Further studies are advised on the identification, physiology, and molecular testing of ginger endophytic actinobacteria.